Integration of Faith and Ecosystems: Islamic Theology as a Foundation for Resistance to Environmental Exploitation in Mandailing Natal - Nur Aisyah; Roni Risky Nasution; Sopi Ade Fariza; Abdul Haris Nasution; Asrofi Asrofi; Zulfahmi Zulfahmi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This article examines the synergy between Islamic theological values and local wisdom as a basis for resistance to environmental exploitation in Mandailing Natal. The focus of the study lies on the application of faith principles, such as the concepts of khalifah, justice, and ihsan, and their implementation through the traditional practice of lubuk larangan. The literature study method was used to collect and analyze secondary data from scientific articles, journals, and national and local news sources. The results of the study show that these Islamic theological values have been deeply rooted in the culture of the Mandailing Natal community, encouraging a critical attitude towards illegal gold mining practices that damage the ecosystem. The lubuk larangan tradition also acts as a mechanism for social control and environmental conservation, by implementing periodic restrictions on extractive activities to provide space for natural regeneration. The findings indicate that the integration of Islamic theology and local wisdom results in a more integrated and ethical natural resource management paradigm. This research recommends strengthening the synergy of faith values and local traditions in the formulation of public policies and increasing community participation in environmental monitoring. This integrative approach can be used as a strategic model to overcome the challenges of environmental exploitation amid increasingly complex global dynamics.